Species-Specific Variation in the B30.2(SPRY) Domain of TRIM5α Determines the Potency of Human Immunodeficiency Virus Restriction - Stremlau, Matthew (American Society for Microbiology, 2005)
Retroviruses encounter dominant postentry restrictions in cells of particular species. Human immunodeficiency virus type 1 (HIV-1) is blocked in the cells of Old World monkeys by TRIM5α, a tripartite motif (TRIM) protein composed of RING, B-box 2, coiled-coil, and B30.2(SPRY) domains. Rhesus monkey TRIM5α (TRIM5α(rh)) more potently blocks HIV-1 infection than human TRIM5α (TRIM5α(hu)). Here, by studying chimeric TRIM5α proteins, we demonstrate that the major determinant of anti-HIV-1 potency is the B30.2(SPRY) domain. Analysis of species-specific variation in TRIM5α has identified three variable regions (v1, v2, and v3) within the B30.2 domain. The TRIM5α proteins of Old World primates exhibit expansion, duplication, and residue variation specifically in the v1 region. Replacement of three amino acids in the N terminus of the TRIM5α(hu) B30.2 v1 region with the corresponding TRIM5α(rh) residues resulted in a TRIM5α molecule that restricted HIV-1 nearly as efficiently as wild-type TRIM5α(rh). Surprisingly, a single-amino-acid change in this region of TRIM5α(hu) allowed potent restriction of simian immunodeficiency virus, a phenotype not observed for either wild-type TRIM5α(hu) or TRIM5α(rh). Some of the chimeric TRIM5α proteins that are >98% identical to the human protein yet mediate a strong restriction of HIV-1 infection may have therapeutic utility. These observations implicate the v1 variable region of the B30.2(SPRY) domain in TRIM5α(rh) antiviral potency.